2009
DOI: 10.1007/bf03175612
|View full text |Cite
|
Sign up to set email alerts
|

Outer membrane vesicle ofNeisseria meningitidis serogroup B as an adjuvant to induce specific antibody response against the lipopolysaccharide ofBrucella abortus S99

Abstract: Brucellosis is a worldwide zoonosis and represents one of the most important public health problems in many countries, especially around the Mediterranean basin, Middle East, India and Central and South America. Currently subunit vaccines are being considered to develop effective vaccines for human which has been evidenced by vaccines currently available against the infections such as meningococcal diseases and influenza .The application of new adjuvants of microbial origins is also underway to design subunit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 24 publications
0
12
0
2
Order By: Relevance
“…Several studies have reported the adjuvant properties of OMVs in the field of vaccine research, namely in cancer vaccines, brucellosis vaccine, tuberculosis (TB) vaccine, meningococcal vaccine, Influenza virus vaccine, hepatitis B vaccine and human immunodeficiency virus (HIV) vaccine. [12,13,21,[23][24][25]. Most of the classic and new adjuvants cause local and systemic hypersensitivity reactions and are not licensed for human use.…”
Section: Universal Adjuvant Properties Of Omvmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported the adjuvant properties of OMVs in the field of vaccine research, namely in cancer vaccines, brucellosis vaccine, tuberculosis (TB) vaccine, meningococcal vaccine, Influenza virus vaccine, hepatitis B vaccine and human immunodeficiency virus (HIV) vaccine. [12,13,21,[23][24][25]. Most of the classic and new adjuvants cause local and systemic hypersensitivity reactions and are not licensed for human use.…”
Section: Universal Adjuvant Properties Of Omvmentioning
confidence: 99%
“…In addition, the adjuvant properties of OMV-derived particles have been demonstrated for potential cancer vaccines [25,27]. Interesting studies in the field of brucellosis subunit vaccines have been carried out by Bhattacharjee et al and Sharifat et al [23,28] which have evaluated group B OMPs (GB-OMV). Brucella melitensis strain 16M LPS non-covalent complex to elicit the immunity against brucellosis in mice.…”
Section: Universal Adjuvant Properties Of Omvmentioning
confidence: 99%
See 1 more Smart Citation
“…OMV de Neisseria meningitidis do sorogrupo B é um dos componentes de origem microbiana mais estudada no que diz respeito à aplicação como adjuvante (Sharifat Salmani et al, 2009;Moshiri et al, 2012). A propriedade adjuvante de OMV proveniente deste e de outros microrganismos vem sendo demonstrada em diversos estudos de desenvolvimento de vacinas.…”
Section: Omv: Aplicação -Adjuvanteunclassified
“…A propriedade adjuvante de OMV proveniente deste e de outros microrganismos vem sendo demonstrada em diversos estudos de desenvolvimento de vacinas. Dentre os principais destacam-se vacinas para a doença causada pelo vírus da influenza (Sharifat Salmani et al, 2009), vírus sincicial respiratório (Etchart et al, 2006), hepatite B (Sardiñas et al, 2006), brucelose (Sharifat Salmani et al, 2009), vírus da herpes genital (Del Campo et al, 2010), para a doença meningocócica tipo B (Tamargo et al, 2013), HIV (Aghasadeghi et al, 2011) e, mais recentemente, têm-se discutido sua aplicação como adjuvante para diferentes tipos de vacinas de câncer (Gujrati e Jon, 2014 Por outro lado, as OMV têm propriedades para apresentar antígenos, além de propriedades adjuvantes, sendo uma estrutura com alto potencial para ser, o que hoje autores denominam, uma plataforma vacinal completa (Gerritzen et al, 2017).…”
Section: Omv: Aplicação -Adjuvanteunclassified